Impact of some organic fertilizers on nutrients uptake, yield of Zucchini (Cucurbita pepo L.) and soil fertility properties - Saudi A. Rekaby; Adel M. Ghoneim; Mostafa Gebreel; Waleed M. Ali; Ahmed F. Yousef; Esawy Mahmoud (Technology in Agronomy)
Maintaining appropriate levels of organic matter is important as it ensures efficient nutrients, which contributes to the sustainable management of sandy soil and crop production. Compost and vermicompost can improve soil fertility and zucchini (Cucurbita pepo L.) production. This study aimed to determine the effects of compost and vermicompost on the yield, and nutrient uptake of zucchini as well as some soil properties under field conditions. The treatments were: control without fertilization (CO), chemical fertilizer (CF), compost (CT), and vermicompost (VC) and were arranged in a randomized complete block design with five replications. The results showed that the compost and vermicompost application significantly increased the yield of zucchini by about 7% and 53%, respectively, in comparison with the chemical fertilizer treatment. In addition, compost and vermicompost treatments significantly increased the soil organic matter, and availability of NPK compared with those in the control and with the chemical fertilizer treatments. The application of the compost and vermicompost amendments increased the total uptake of NPK compared with the control and chemical fertilizer treatments. The highest values of N, P, and K use efficiency were found in the compost treatment. Compost and vermicompost application increased the zucchini yield compared with other treatments. Fruit weight increased by about 1%, 5%, and 8%, respectively, in the chemical fertilizer, vermicompost, and compost treatments, while fruit length increased by about 24%, 10%, and 13%, respectively.